Iron Transporters and Ferroptosis in Malignant Brain Tumors - Zhao, Jingyu; Wang, Yaqi; Tao, Lei; Chen, Ligong (Frontiers in Oncology, 2022)
Malignant brain tumors represent approximately 1.5% of all malignant tumors. The survival rate among patients is relatively low and the mortality rate of pediatric brain tumors ranks first among all childhood malignant tumors. At present malignant brain tumors remain incurable. Although some tumors can be treated with surgery and chemotherapy, new treatment strategies are urgent owing to the poor clinical prognosis. Iron is an essential trace element in many biological processes of the human body. Iron transporters play a crucial role in iron absorption and transport. Ferroptosis, an iron-dependent form of nonapoptotic cell death, is characterized by the accumulation of lipid peroxidation products and lethal reactive oxygen species (ROS) derived from iron metabolism. Recently, compelling evidence has shown that inducing ferroptosis of tumor cells is a potential therapeutic strategy. In this review, we will briefly describe the significant regulatory factors of ferroptosis, iron, its absorption and transport under physiological conditions, especially the function of iron transporters. Then we will summarize the relevant mechanisms of ferroptosis and its role in malignant brain tumors, wherein the role of transporters is not to be ignored. Finally, we will introduce the current research progress in the treatment of malignant brain tumors by inducing ferroptosis in order to explain the current biological principles of potential treatment targets and treatment strategies for malignant brain tumors.